Angiotensin type-1 receptor autoantibodies promote alpha-synuclein aggregation in dopaminergic neurons - Lage, Lucia; Rodríguez-Perez, Ana I.; Labandeira-Garcia, Jose L.; Dominguez-Meijide, Antonio (Frontiers in Immunology, 2024)
Angiotensin, through its type-1 receptor (AT1), is a major inducer of inflammation and oxidative stress, contributing to several diseases. Autoimmune processes have been involved in neurodegeneration, including Parkinson’s disease (PD). AT1 autoantibodies (AT1-AA) enhance neurodegeneration and PD, which was related to increased neuronal oxidative stress and neuroinflammation. However, the effect of AT1-AA on α-synuclein aggregation, a major factor in PD progression, has not been studied. In cultures of dopaminergic neurons, we observed that AT1-AA promote aggregation of α-synuclein, as AT1-AA upregulated major mechanisms involved in the α-synuclein aggregation process such as NADPH-oxidase activation and intracellular calcium raising. The results further support the role of AT1 receptors in dopaminergic neuron degeneration, and several recent clinical studies observing the neuroprotective effects of AT1 receptor blockers.